Two new species of Pagurixus (Crustacea: Decapoda: Anomura: Paguridae) from submarine caves of the Ryukyu Islands, southwestern Japan - Osawa, Masayuki; Fujita, Yoshihisa; Okuno, Junji (Zootaxa, 2006)
Two new species of Pagurixus Melin, 1939, P. pulcher and P. longipes, are described from the submarine caves of the Ryukyu Islands, southwestern Japan. These species belong to the different informal species group of the genus characterized by the presence or absence of two distinct, longitudinal rows or series of setae on the ventral surface of the antennular ultimate segment. Pagurixus pulcher is most closely allied to P. nomurai Komai & Asakura, 1995, but is differentiated by the more slender ocular peduncles, setation on the ultimate segment of the antennular peduncle, and shape of the anterior lobe of the sixth thoracic sternite. The extremely long and slender carpus of the left cheliped and dactyli of the ambulatory pereopods clearly distinguish P. longipes from other species belonging to the species group characterized by the absence of longitudinal rows or series of setae on the ventral surface of the antennular ultimate segment.